An experimental investigation evaluating the protective effect of a hydroalcoholic extract of the aerial portion of Alenda (Ephedra fragilis Desf.) against hepatotoxicity caused by mercaptopurine in rats - Afaf H. Al-Nadaf, Nisreen Abu Shahin, Areej Awadallaha, Raghd Obidat, Samia Arman, Samar Thiab (Journal of Applied Pharmaceutical Science, 2025)
Chemical hepatotoxicity can lead to various liver illnesses, including hepatitis and cirrhosis. Mercaptopurine (MP) is a potent anti-tumor medication, but its use is restricted due to its potential adverse effects, such as myelotoxicity. Plants naturally contain hepatoprotective phytoconstituents that protect the liver from hepatotoxicity and promote liver regeneration. The purpose of the study is to investigate the potential protective impact of hydroalcoholic arial component extract from Ephedra fragilis Alenda (E. fragilis) against MP-induced liver damage in rats. Rats were randomly assigned to seven groups. Silymarin at 50-mg.kg−1 b.w., MP at 40-mg.kg−1 b.w., E. fragilis extract 30-mg. kg−1 b.w., E. fragilis extract 30 mg.kg−1 and MP 40 mg.kg−1, Silymarin 50 mg.kg−1 and MP 40 mg.kg−1, E. fragilis extract (15 mg.kg−1), silymarin dose of 25 mg.kg−1, and MP 40 mg.kg−1 were given to the control group. On days 0, 10, and 21, blood samples were taken. The study used serum biochemical markers such as albumin, bilirubin, liver enzymes, and total protein to measure liver damage and histopathological alterations. In rats treated with MP, the administration of E. fragilis extract decreased bilirubin and alkaline phosphatase levels. Histopathological analysis of livers revealed that E. fragilis extract decreased necrosis, fatty degeneration, and andation in MP-treated rats. These findings indicate that E. fragilis extract potentially protects against liver injury in rats caused by MP. It has a possible protective effect against drug-induced cholestasis. These findings show that Alenda extract might be an effective hepatoprotective agent for improving hepatocellular damage.
Keywords: Alenda., Ephedra fragilis, aerial part, hepatoprotective, mercaptopurine, hydroalcoholic extract